Plasma Levels of Tumor Necrosis Factor-Alpha and Interleukin-6 in Obsessive Compulsive Disorder - N. Konuk; I. O. Tekın; U. Ozturk; L. Atik; N. Atasoy; S. Bektas; A. Erdogan (Hindawi Limited, 2007)
Aim. Recent research implicated place of an immune mechanism in the pathophysiology of obsessive-compulsive disorder (OCD). Despite increasing evidence involvement of cytokine release in OCD, results of the studies are inconsistent. The aim of this study was to evaluate the plasma levels of the cytokines; tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) in OCD patients. Methods. Plasma concentrations of TNF-α and IL-6 were measured in 31 drug-free outpatients with OCD, and 31-year age and sex-matched healthy controls. TNF-α and IL-6 concentrations in blood were determined by enzyme-linked immunosorbent assay (ELISA). Results. Both TNF-α and IL-6 levels showed statistically significant increases in OCD patients compared to controls (P<.000, P<.001, resp.). In addition, the age of onset was negatively correlated with TNF-α level (r=−.402, P=.025) and duration of illness was weakly correlated with IL-6 levels (r:.357; P:.048) in patients group. Conclusion. OCD patients showed increases in TNF-α and IL-6 levels compared to the healthy controls. This study provides evidence for alterations in the proinflamatory cytokines which suggest the involvement of the immune system in the pathophysiology of OCD.